Epithelioid Inflammatory Myofibroblastic Sarcoma Presenting as Gastrointestinal Bleed: Case Report and Literature Review. Issue 1 (17th February 2021) - Giannaki, Alexandra; Doganis, Dimitrios; Giamarelou, Panagiota; Konidari, Anastasia
Abstract : Myofibroblastic tumor is a mesenchymal neoplasm composed of myofibroblastic spindle cells with inflammatory infiltrate and considered to be of low-malignant potential tumor. Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a variant of myofibroblastic tumor with malignant characteristics; it mainly consists of round-to-epithelioid cells with positive nuclear membrane/perinuclear immunostaining for anaplastic lymphoma kinase (ALK) receptor tyrosine kinase. A gastric EIMS case in a 7-year-old boy is discussed. Our patient presented with severe anemia and melena. Magnetic resonance imaging of the abdomen and pelvis revealed a solid tumor (2.7 × 1.9 × 2.6 cm) at the posterior stomach wall. Upper gastrointestinal endoscopy revealed an irregular, protruding, highly vascular, approximately 2 cm mass close to the gastrooesophageal junction. Endoscopic biopsies were taken for histology; tumor cells were epithelioid with eccentric nuclei, prominent nucleoli, and abundant eosinophilic cytoplasm. Immunohistochemistry showed positive staining for desmin, smooth muscle actin, epithelial membrane antigen, cluster of differentiation CD30, and strongly positive staining for ALK. Fluorescence in situ hybridization analysis confirmed the presence of ALK rearrangements. A full-thickness surgical excision of the tumor with clear margins was performed. No adjunct treatment was administered and our patient has remained in full remission at 12 months following the surgery. To the best of our knowledge, this is the first pediatric case of gastric EIMS. Raised awareness and prompt recognition of special histological and immunochemical characteristics of EIMS can lead to accurate diagnosis and targeted therapy.